Reduction of dissolved oxygen in minimizing corrosion - Mary Grace Ventanilla; Jason Ongpeng; Nishida Takahiro; Keiyu Kawaai (Acta Polytechnica CTU Proceedings, 2022)
Concrete structures are susceptible to corrosion especially when exposed to marine environment. In order to minimize the corrosion in reinforced concrete, reduction of dissolved Oxygen (DO) in mixing water is recommended. The DO is the measurement of the amount of free Oxygen that is dissolved in water which is proportional to the corrosion rate of steel bars inside concrete. In this paper, the use of industrial waste/by-products, agricultural waste, natural minerals, and green inhibitors as additive for cement in reducing the DO level of the mixing water was explored. Candidate materials from different types of agricultural waste, industrial waste, natural minerals, and green inhibitors. The percentage difference of DO were computed for all types of materials as ash or powder or extract in room temperature. This is the percentage difference of DO level in distilled water and the solution mixed with the candidate material having a mass ratio of 3 : 2 and/or 3 : 1. Results showed that more than 90% reduction of DO level were achieved when mixed with ginger extract, ginger powder, aloe vera extract, ginger pulp, and rice hull ash. Future experimental studies using the candidate materials producing reinforced concrete specimens with high reduction of DO level in mixing water is recommended.